Municipal Labour Demand - Sweden 1988 - 1995 - Pål Bergström; Matz Dahlberg; Eva Johansson (Uppsala University, Department of Economics, 1998)
In this paper we investigate the determinants of municipal labour demand in Sweden 1988-1995. Utilising a major grant reform in 1993, through which a switch from mainly targeted to mainly general central government grants occurred, we are able to identify which type of grants that have the largest effects on municipal employment. We find a larger municipal employment elasticity with respect to grants before the reform, implying that the more freedom given to the municipalities, the less they seem inclined to spend on municipal employment. We further find (i) a short run wage elasticity of approximately -0.5 and a long run ditto of approximately -0.9, (ii) a quite sluggish adjustment process: only 60% of the desired change in municipal employment is implemented in the first year, (iii) that the demographic structure is an important determinant of municipal employment, and (iv) that the behavioural pattern is different in socialist municipalities.
urn:nbn:se:uu:diva-2437
Keywords: C23; H70; J45; 330; Municipal labour demand; Panel data; Median voter model; Sluggishness